ADR holdings of US-based emerging market funds - Aggarwal, Reena; Dahiya, Sandeep; Klapper, Leora (Journal of Banking & Finance, 2007)
What motivates investors to hold American Depositary Receipts (ADRs) rather than the underlying stock of US listed foreign firms? We analyze the investment allocation decision of actively-managed emerging market mutual fund managers. Although legal provisions are typically assumed to affect ADR and its underlying domestic shares equally, investors holding ADRs may have a higher level of legal protection as these securities are issued and traded in the US. We find that ADRs are the preferred mode of holdings if the local market of the issuer has weak investor protection, low liquidity and high transaction costs.